Teste empírico do modelo CAPM: aplicação da não linearidade para o mercado brasileiro de capitais - MOURA, Malu Brandão (2016)
This work test the CAPM Model to Brasilian market given limitations of it and considering that it is possible the non linearity existence to the precification of the assets to catch the interferences of variables that are not considered at linear version of this model. The mainly objective is analysing how the assets’ value answer to high and low moviments in this Market and what is the reaction as well as understand if the non linearity to CAPM Model is more eficiente to price the assets in the Brasilian Capital Market. The analyse was possible with the the regression test applicated to the assets of the mainly index of the BM&FBOVESPA, IBrX50. The propose is identify asymmetries’ behaviors at this context. In this sense, the monthly returns were used at the period between January 2005 and May 2015. It was found that the degree of asymmetry of the assets that make up the IBrX50 is not high, but this fact does not invalidate the CAPM, shows that by adding other significant variables and highlight the non-linearity of the market in question, its use is justified for this type of analysis. The results also demonstrate the sensitivity of investors to market changes, confirming the fact of loss aversion .